LEGAL PROTECTION FOR SURGEONS AGAINST MEDICAL NEGLIGENCE RESULTING IN PERMANENT DISABILITY IN PATIENTS - Carolina Kuntardjo; Marsudi Dedi Putra; Imam Ropii; Ida Bagus Tatwa Yatindra (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
This study examines the legal protection afforded to surgeons in cases of medical negligence resulting in permanent disability to patients within the Indonesian legal system. The issue arises from the high-risk nature of surgical procedures, where adverse medical outcomes are often directly associated with legal liability, potentially leading to the criminalization of medical professionals. This research employs a normative legal research method using a qualitative approach, incorporating statutory and case approaches through the analysis of legislation, court decisions, and legal doctrines related to medical malpractice. The findings indicate that surgeons’ liability for medical negligence is regulated through a layered legal regime encompassing criminal, civil, and professional disciplinary mechanisms as stipulated in Law Number 17 of 2023 on Health, the Criminal Code, and the Civil Code. The study further reveals that legal protection for surgeons is conditionally provided when medical actions comply with professional standards, standard operating procedures, and ethical principles, supported by mechanisms such as informed consent and professional disciplinary review. Ultimately, the regulation of medical negligence aims to ensure patient rights recovery while preventing excessive criminalization of the medical profession, thereby maintaining the sustainability and quality of healthcare services.